Utilization of central composite design in optimization of microbial growth inhibition using ananas comosus leaves juice - Amirah, Ya’acob; N., Zainol (IOP Publishing, 2021)
Microbial growth inhibitors have been very effective for the prevention of disease transmission and infection. For this study, pineapple (Ananas comosus) leaves juice (PLJ) was use as microbial growth inhibitor (MGI) because of its higher phenolic content. Microbe from contaminated pineapple leaves was use as tested microbe. The selected operating conditions in this study were temperature and microbial inhibition time with the range between 35 to 39 °C and 10 to 50 min respectively. Microbial growth inhibition experimental design set-up was constructed using Design Expert software (Version 7.1.6) to analyze the condition required. The experiments was conducted according to the central composite design (CCD) in two variables of the surface response methodology (RSM) to determine the optimum conditions for inhibiting microbial growth. Quadratic polynomial model was constructed to predict the microbial growth inhibition. A quadratic polynomial model was generated to predict microbial growth inhibition. Microbial growth inhibition was measured using the method of colony formation unit (CFU) counting. The RSM result showed that microbial inhibition time had a major impact on inhibition of microbial development. The optimum conditions were 37 °C and 34.25 min with a 94.73% microbial growth inhibition. In this condition, microbe growth was predicted to be at a minimum rate due to inhibition of the phenolic compound in PLJ. The optimum state of this study will be useful for the use of PLJ in pineapple plantation.